Shifts in bacterial communities of eggshells and antimicrobial activities in eggs during incubation in a ground-nesting passerine. - Stéphanie Grizard; Maaike A Versteegh; Henry K Ndithia; Joana F Salles; B Irene Tieleman (PLoS ONE, 2015)
Microbial invasion of egg contents is a cause of embryonic death. To counter infection risks, the embryo is protected physically by the eggshell and chemically by antimicrobial proteins. If microbial pressure drives embryo mortality, then females may have evolved, through natural selection, to adapt their immune investment into eggs. Although frequently hypothesized, this match between immune allocation and microorganisms has not been explored yet. To examine if correlations between microbes on eggs and immunity in eggs exist, we collected eggs from red-capped larks (Calandrella cinerea) and simultaneously examined their bacterial communities and antimicrobial components--pH, lysozyme and ovotransferrin--during natural incubation. Using molecular techniques, we find that bacterial communities are highly dynamic: bacterial abundance increases from the onset to late incubation, Shannon's α-diversity index increases during early incubation stages, and β-diversity analysis shows that communities from 1 day-old clutches are phylogenetically more similar to each other than the older ones. Regarding the antimicrobials, we notice a decrease of pH and lysozyme concentration, while ovotransferrin concentration increases during incubation. Interestingly, we show that two eggs of the same clutch share equivalent immune protection, independent of clutch age. Lastly, our results provide limited evidence of significant correlation between antimicrobial compounds and bacterial communities. Our study examined simultaneously, for the first time in a wild bird, the dynamics of bacterial communities present on eggshells and of albumen-associated antimicrobial components during incubation and investigated their relationship. However, the link between microorganisms and immunity of eggs remains to be elucidated further. Identifying invading microbes and their roles in embryo mortality, as well as understanding the role of the eggshell microbiome, might be key to better understand avian strategies of immune maternal investment.